THE INFLUENCE OF PROMOTION STRATEGY, PRICE AND PRODUCT QUALITY ON PURCHASE DECISION OF PROCESSED SOYBEAN PRODUCTS IN INDONESIA - Luh Komang Candra Dewi; Muthi’atul Khasanah; Ratnawita Ratnawita; Kunto Atmojo; NPMA Durya (Jurnal Scientia, 2023)
Rumah Tempe Indonesia is a company engaged in the soybean processing industry. The purpose of this study is to investigate the direct impact of product quality, pricing, and marketing on interest and purchase decisions. The sample consisted of 100 Indonesian tempe house patrons who were chosen using a purposive sampling approach. According to the findings of this study, product quality has a positive and significant influence on product buy interest, however price and promotion have no positive and significant effect on product purchase interest. Product quality and promotion have a positive and substantial impact on product purchasing decisions, but price has no negative and major impact; purchase interest has a positive and significant impact on product purchasing decisions; purchase interest mediates product quality on product purchasing decisions, while purchase interest does not mediate prices and promotions on product purchasing decisions.